Internationalization of Legal Education in Indonesia: Insights from Faculty of Law Universitas Negeri Semarang - Sastroatmodjo, Sudijono; Muhtada, Dani (The Indonesian Journal of International Clinical Legal Education, 2019)
todayÃ¢â‚¬â„¢s global era. While the internationalization of higher educationhas been defined as Ã¢â‚¬Å“the process of integrating an international,intercultural and global dimension into the goals, teaching/learning,research and service functions of a university or higher educationsystemÃ¢â‚¬Â (Knight, 2014), the internationalization of legal education refersto such a process at the schools of law around the world. Severalfactors have contributed to the increasing need for such aninternationalization of legal education. These factors include theincreasing demand for transnational legal practices and the emergenceof legal problems that occurred across international boundaries. Thisarticle discusses the internationalization of legal education in Indonesia,focusing on the practice of international program offered by Faculty ofLaw at Universitas Negeri Semarang. The article analyzes the strengthsand opportunity of the program as well as its weaknesses and threats.The picture of the international program at the Faculty of Law atUniversitas Negeri Semarang may not reflect the general picture of theinternational programs in many Faculties of Law at Indonesianuniversities. However, it can provide a glance on how theinternationalization of legal education has been practiced by a publicuniversity in Indonesia. The article starts with a discussion ontheoretical views on the internationalization of legal education. Then itpresents why internationalization of legal program is needed and howit should be practiced in the Indonesian context. It then provides acritical analysis on the practice of international law program atUniversitas Negeri Semarang. Some strengths and weaknesses of theprogram are discussed. A recommendation to improve the quality ofthe international program at the Indonesian Faculties of Law ispresented afterwards.